Effects of smoking on non‐surgical periodontal therapy in patients with periodontitis Stage III or IV, and Grade C. Issue 4 (14th September 2019) - Kanmaz, Burcu; Lappin, David F.; Nile, Christopher J.; Buduneli, Nurcan
Abstract: Background: To evaluate possible effects of smoking on clinical, biochemical, and microbiological outcomes of non‐surgical periodontal treatment in patients with periodontitis Stage III or IV and Grade C. Methods: Conventional quadrant‐wise non‐surgical periodontal treatment was performed and whole‐mouth periodontal measurements were recorded at baseline, 1, 3, and 6 months after completion of treatment. Saliva, gingival crevicular fluid, subgingival plaque, and blood samples were obtained at the same time points. Inflammatory cytokine levels, presence, and quantities of 11 different bacterial species were determined. Smoking status was validated by cotinine assay. Results: Fourteen smoker and 13 non‐smoker patients completed the study protocol and revealed similar clinical findings except for the higher plaque scores in the non‐smokers at 6 months ( P <0.01). Significant differences were found between the study groups in biofluid cytokine levels at 1 and 3 months ( P <0.01). Gram‐negative bacteria were more abundant in the smokers at baseline and so were Gram‐positive bacteria in the non‐smokers ( P <0.01). Gram‐negative bacteria repopulated in the smokers faster than in the non‐smokers ( P <0.01). Conclusions: The present findings suggest that smoker patients with periodontitis Stage III and IV, Grade C respond well to the non‐surgical periodontal treatment during the 6‐month follow‐up. However, smokers exhibit faster repopulation of Gram‐negative bacteria.